A quantification of behavioural mistakes by retail investors - Řehulka, David (2023)
Behavioural finance, a subfield of finance, studies the decisions and behavioural patterns of investors, linking them back to cognitive psychology. Daniel Kahneman, Amos Tversky, and other pioneers of this field have been laying out the foundations for over 40 years, since the late 1970s, although earlier evidence of this approach can be found as well. The discipline focuses on the idea that investors are not always logical, that self-control has its limits, and that investors are impacted by their own biases, all of which have an impact on the markets. The goal of this thesis is to provide a simple introduction to the world of contemporary behavioural economics, present clear explanation of the key behavioural biases and showcase the role of such irrational behaviour in the formation in several market bubbles. Furthermore, this paper will discuss alternative investment strategies that can be employed by retail investors, with emphasis on their potential risks. Finally, my research conducted among over two hundred retail investors will demonstrate the prevalence of chosen behavioural biases and heuristics, as well as offer methods to help avoid these mistakes and consequently lead to better financial decisions, thus adding value to the current discourse.